2007
DOI: 10.1590/s0104-66322007000100011
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic model for the first stage of pygas upgrading

Abstract: -Pyrolysis gasoline -PYGAS -is an intermediate boiling product of naphtha steam cracking with a high octane number and high aromatic/unsaturated contents. Due to stabilization concerns, PYGAS must be hydrotreated in two stages. The first stage uses a mild trickle-bed conversion for removing extremely reactive species (styrene, dienes and olefins) prior to the more severe second stage where sulfured and remaining olefins are hydrogenated in gas phase. This work addresses the reaction network and two-phase kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…PYGAS is a product in the naphtha boiling range, with carbon numbers between C 5 -C 11 , with a high content of aromatics and olefins. It is used for blending with gasoline or as a raw material for the extraction of benzene, toluene and xylene (BTX) [3]. In this context, due to the increasing world trend towards the processing of heavier and cheaper raw materials for the generation of light olefins, the problem arises of finding use for growing stocks of PYGAS.…”
Section: Introductionmentioning
confidence: 99%
“…PYGAS is a product in the naphtha boiling range, with carbon numbers between C 5 -C 11 , with a high content of aromatics and olefins. It is used for blending with gasoline or as a raw material for the extraction of benzene, toluene and xylene (BTX) [3]. In this context, due to the increasing world trend towards the processing of heavier and cheaper raw materials for the generation of light olefins, the problem arises of finding use for growing stocks of PYGAS.…”
Section: Introductionmentioning
confidence: 99%
“…However, the DE values microspheres containing EC (80.48%) showed that they were statistically more significant than commercial tablet (P < 0.05). The in vitro release profiles were fitted on various kinetic models in order to find out the mechanism of drug release (17,18). The fit parameters to Higuchi, first order, Peppas and zero order equations are given in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…In the first set of experiments, the temperature was fixed at 80 °C, which is inside the temperature range of 50 -130 °C used industrially (Medeiros et al, 2007). Five levels of H2 pressure (16,26,36,46, and 56 bar) and three levels of styrene concentration (0.3, 0.5 and 0.8 mol/L) were used.…”
Section: Styrene Hydrogenationmentioning
confidence: 99%
“…In the first one, styrene and diolefins are selectively hydrogenated under moderate conditions to prevent gum and coke formation. The reactor temperature and hydrogen pressure are in the range of 50 -130 °C and 20 -40 bar, respectively (Cheng et al, 1986;Medeiros et al, 2007). In the second stage, sulfur compounds are converted and mono-olefins are hydrogenated using higher temperatures (Mostoufi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%